Young onset dementia: Public involvement in co-designing community-based support. (May 2020) - Mayrhofer, Andrea M; Mathie, Elspeth; McKeown, Jane; Goodman, Claire; Irvine, Lisa; Hall, Natalie; Walker, Michael
Whilst the support requirements of people diagnosed with young onset dementia are well-documented, less is known about what needs to be in place to provide age-appropriate care. To understand priorities for service planning and commissioning and to inform the design of a future study of community-based service delivery models, we held two rounds of discussions with four groups of people affected by young onset dementia (n = 31) and interviewed memory services (n = 3) and non-profit service providers (n = 7) in two sites in England. Discussions confirmed published evidence on support requirements, but also reframed priorities for support and suggested new approaches to dementia care at the community level. This paper argues that involving people with young onset dementia in the assessment of research findings in terms of what is important to them, and inviting suggestions for solutions, provides a way for co-designing services that address the challenges of accessing support for people affected by young onset dementia.